Impact of the sustainability report on Hungarian stock prices - Tömöri, Gergő; Lakatos, Vilmos (Competitio, 2024)
ESG reporting has become increasingly significant for evaluating corporate sustainability. Our study examined firms that had been publicly listed for several years by 2023, and which had already engaged in ESG reporting voluntarily, showing an early, consistent commitment to sustainability despite the absence of regulatory requirements. We hypothesised that this group’s market valuation metrics would reflect a more favourable and realistic investor assessment compared to a control group. However, our findings revealed that while statistically significant differences appeared primarily in the Price-to-Book Value (P/BV) ratios, overall, the investor assessments did not yet demonstrate a statistically significant divergence on average. This may suggest that ESG reports serve more as marketing tools than as indicators of genuine sustainable resource management, which some investors recognise from other mandatory financial disclosures. These insights can support further research on the Hungarian investment climate and aid in refining EU sustainability directives within Hungary’s regulatory framework.JEL classification code: Q56, G11